Goal-directed control on interval schedules does not depend on the action-outcome correlation - Garr, Eric (J Exp Psychol Anim Learn Cogn, 2019)
When an organism’s action is based on an anticipation of its consequences, that action is said to be goal-directed. It has long been thought that goal-directed control is made possible by experiencing a strong correlation between response rates and reward rates (Dickinson, 1985). To test this idea, we designed a set of experiments to determine whether the response rate-reward rate correlation is a reliable predictor of goal-directed control on interval schedules. In Experiment 1, rats were trained on random interval (RI) schedules in which the response rate-reward rate correlation was manipulated across groups. In tests of reward devaluation, rats behaved in a goal-directed manner regardless of the experienced correlation. In Experiment 2, rats once again experienced either a strong or weak correlation, but on RI schedules with lower overall reward densities. This time, behavior appeared habitual regardless of the experienced correlation. Experiment 3 confirmed that the density of the RI schedule influences goal-directed control, and also revealed that extensive training on these schedules resulted in goal-directed action. Finally, in Experiment 4 goal-directed responding was greater and emerged sooner on fixed than random interval schedules, but, again, was manifest after extensive training on the RI schedule. Taken together, our data suggest that goal-directed and habitual control are not determined by the correlation between response rates and reward rates. We discuss the importance of temporal uncertainty, action-outcome contiguity, and reinforcement probability in goal-directed control.